The Influence of Product Quality, Price, and Promotion on Repurchase Intention on Tiktok Shop Among Students of Universitas Prima Indonesia - Richard Albert; Michael Novtriandy Sidabutar; Melfrianti Romauli Purba; Nasib Nasib (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to determine the effect of product quality, price, and promotion on repurchase intention on TikTok Shop among students of Universitas Prima Indonesia. The background of this research is based on the rapid growth of social commerce, especially TikTok Shop, which has influenced changes in consumer purchasing behavior. However, repurchase intention is still influenced by several factors such as product quality, price, and promotional effectiveness. This research uses a quantitative method with a survey approach. The population in this study consists of 17,289 students of Universitas Prima Indonesia, with a sample size of 100 respondents determined using the Slovin formula. The sampling technique used is purposive sampling, with criteria of students who have made repurchases on TikTok Shop. Data collection was conducted through questionnaires, and data analysis was performed using multiple linear regression. This study aims to determine the effect of product quality, price, and promotion on repurchase intention on TikTok Shop among students of Universitas Prima Indonesia. The background of this research is based on the rapid growth of social commerce, especially TikTok Shop, which has influenced changes in consumer purchasing behavior. However, repurchase intention is still influenced by several factors such as product quality, price, and promotional effectiveness. This research uses a quantitative method with a survey approach. The population in this study consists of 17,289 students of Universitas Prima Indonesia, with a sample size of 100 respondents determined using the Slovin formula. The sampling technique used is purposive sampling, with criteria of students who have made repurchases on TikTok Shop. Data collection was conducted through questionnaires, and data analysis was performed using multiple linear regression.